Disorientasi Harmonisasi Rumah Tangga dalam Keluarga Muslim di Era Digital - Sarkowi Sarkowi; Marzuki Marzuki; Fajar Kamizi; Hana Pertiwi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
Islamic studies with an astronomical approach are interesting and important, because the history of the development of Muslims in religious practice cannot be separated from the astronomical field as well as advanced technology and also science. This journal aims to reveal three things are: first, the understanding of the astronomical approach second, methods, techniques, and research steps in the astronomical approach third, the implementation of the astronomical approach in Islamic studies. The method used is a literature study by digging from primary and secondary books as well as national and international scientific journals. The results of this study indicate are: first, etymologically astronomy comes from the Greek, namely Astron (ἄστρον, “star”) and Nomos (νόμος law/culture). According to the term is the science of calculation or almanac determination, the physical and chemical properties of objects that can be seen in the sky and beyond the earth. Second, the research method used in the astronomical approach is literature study and observation. Third, among the implementations, namely the application of determining Islamic dates, the application of the cardinal directions in determining the Qibla direction, application in weather prediction, as well as the sun, stars, moon in predicting sunny weather, rain or eclipses.